Referenčni model strukture delov košarkarske igre - Dežman, Brane (Šport (Ljubljana), 2010)
This article proposes a model structure of the game of basketball. In the opening part, the model, its phases and sub-phases are presented and defined according to the rules of the game. The second part of the article is experimental: on a sample of 20 quarters from five games of the U20 European Championship for Men played in Nova Gorica and Goriyia in 2007, we studied the frequency and average length of each distinct phase and sub-phase.
Keywords: analiza igre; košarka; struktura